Panduan Transenden Guna Mendorong Kesejahteraan Spiritual Melalui Pastoral Konseling - Herman, Samuel; Senjaya, Styadi (Universitas Sanata Dharma, 2024)
Pastoral counseling plays a vital role in guiding and nurturing the congregation, employing a holistic approach grounded in Christian faith principles. Pastoral counseling not only serves as an advisor but also as a spiritual companion capable of addressing the emotional and behavioral aspects of the counselee. Balancing attention to both aspects, in line with pastoral theology, provides a solid foundation for a ministry committed to spiritual recovery, growth, and transformation. The use of the Bible as the primary guide requires wisdom in applying God's Word according to its context and meaning. Balancing present-day considerations with those of the past, and understanding sin, repentance, and forgiveness as fundamental to pastoral theology, form the basis of an effective counseling approach. The stages of counseling, the role of the counselor as a representative of Christ, and the wise use of the Bible create a solid foundation for effective counseling. This study employs a qualitative phenomenological method with literature review. Data analysis includes management, reading, description, interpretation, and representation. An inductive approach is used to formulate conclusions and predictions, supporting exploration in the context of pastoral counseling. Integrating psychology, humanities, and deep theology helps counselors understand the complexity of counselees holistically. Through critical evaluation and adaptation of the approach, pastoral counseling has a positive and sustainable impact on the spiritual growth and well-being of the congregation members. Pastoral counseling illustrates the church's commitment to guiding the congregation toward deep spiritual growth and well-being.